Effects of Electroacupuncture Combined With Psychological Intervention on Depressive Status and Contingent Negative Variation in Patients With Internet Addiction Disorder: A Randomized Controlled Trial - Peng, Wei; Wang, Yang; Hao, Qinghong; Wang, Jun; Chen, Yalin; Qiu, Mimi; Tu, Yang; Li, Hui; Zhu, Tianmin (Frontiers in Psychiatry, 2021)
Background: Depressive symptoms often accompany people with Internet addiction syndrome (IAD). Acupuncture has been found to have significant advantages in improving the severity and depressive symptoms of IAD. Contingent negative variation (CNV) is a common method to explore the mechanism of neurophysiology. Objective: The purpose of this study was to observe the efficacy of electroacupuncture (EA), psychological intervention (PI), and comprehensive intervention (CI) in the treatment of depression in Internet addiction disorder (IAD), and to observe the changes of contingent negative variation (CNV) in each group. Methods: 120 subjects diagnosed with IAD were randomly assigned to the EA group, the PI group, or the CI group. They received EA, PI, or a combination of EA and PI for 40 days. The Internet Addiction Test (IAT), the Zung Self-rating Depression Scale (SDS), and the Hamilton Depression Scale (HAMD) were evaluated for all subjects at baseline, 20th, and 40th days of treatment, while CNV data were collected at baseline and 40th days of treatment. Results: Three treatments effectively reduced IAT, SDS, and HAMD scores, and the intergroup comparison showed that CI was superior to EA, while EA was superior to PI. CNV results indicated that the CNV amplitude increased in all three groups of IAD patients after treatment. The CNV latency of point A and A-S2’ wave area of the EA group and the CI group did not change significantly after treatment. Only the A-S2’ wave area of the PI group increased significantly compared with the baseline period. In addition, IAD's IAT score was positively correlated with SDS and HAMD score at baseline but negatively correlated with CNV latency. After treatment, only the change of HAMD score in the CI group was negatively correlated with amplitude. Conclusion: Our results demonstrate the efficacy of acupuncture and psychological intervention in the treatment of IAD from an electrophysiological perspective. Simultaneously, the increase in CNV amplitude might be the underlying neurophysiological mechanism by which CI improves depression and cognitive function in IAD patients.